PENGEMBANGAN APLIKASI INSTRUMEN ANALISIS BUTIR SOAL KUESIONER BERBASIS TEKNOLOGI INFORMASI - M.Nasrullah; Muhammad Kris Yuan Hidayatullah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The objective of this research is to create a desktop application that can analyze questionnaire items. The next phase involves assessing the feasibility of the Anabus Application for analyzing questionnaire items by gathering feedback from media experts and teachers. This research follows the Research and Development (R&D) model, specifically adapted from the ADDIE development model.The ADDIE model consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The model was validated by media experts and tested on 30 teachers at MTs Thoriqul Huda Catakgayam Mojowarno Jombang. The research results indicate that the Anabus Questionnaire application's feasibility is based on the assessments. The first media expert scored 42, falling into the "Not good" category, but the presentation received a 70% score, placing it in the "Decent" category. The second media expert scored 55, which is in the "Good" category, with a 92% score, placing it in the "Very Decent" category. The third media expert achieved a score of 54, which is in the "Good" category with a 90% score, also in the "Good" category. The teachers' response to the Anabus application during the trial was 73%. Therefore, the desktop-based Anabus Questionnaire application is suitable for analyzing question items in educational institutions.